Positive active particle, positive pole piece and solid-state battery
By designing positive electrode active particles with active cores, adhesion layers and cladding layers, the problem of low electrical performance of all solid-state batteries is solved, and the effect of improving the dynamic performance and cycle capacity retention rate of solid-state batteries is achieved.
Patent Information
- Application Number
- CN202411803299.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-03-11
AI Technical Summary
Because of the use of solid electrolytes, all-solid-state batteries reduce the ionic conductivity and electronic conductivity, which in turn reduces the electrical performance of solid-state batteries.
A positive electrode active particle is designed, including an active core, an adhesion layer and a cladding layer. The active core consists of the first active particle, the second active particle and the first solid electrolyte. By adjusting the particle size and composition, the contact area and ion transport efficiency between the particles are improved. The adhesion layer and the cladding layer further enhance the mechanical strength and electrochemical properties of the particles.
By improving the ionic conductivity and electron conductivity of the positive electrode active particles, the kinetic performance of the solid-state battery is enhanced and its circulation capacity retention rate is improved.
Smart Images

Figure CN119601639A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of energy storage, and specifically to a positive electrode active particle, a positive electrode plate and a solid-state battery. Background Art
[0002] As a new type of battery technology, solid-state batteries have broad development prospects and market demand. In the future, with the continuous advancement of technology and the increase in market demand, solid-state batteries are expected to be widely used and become one of the important development directions in the field of energy storage. Since all-solid-state batteries use solid electrolytes to replace all liquid electrolytes, their ionic conductivity and electronic conductivity are significantly reduced, which reduces the electrical performance of solid-state batteries. Summary of the invention
[0003] In a first aspect, an embodiment of the present application provides a positive electrode active particle, wherein the positive electrode active particle comprises:
[0004] An active core, the active core comprising first active particles, second active particles and a first solid electrolyte, the average particle size of the first active particles being larger than the average particle size of the first solid electrolyte, and the average particle size of the first solid electrolyte being larger than the average particle size of the second active particles;
[0005] an adhesion layer, the adhesion layer wrapping the surface of the active core; and
[0006] The coating layer is wrapped around the surface of the adhesion layer.
[0007] Furthermore, the average particle size of the first active particles is Dv150, and the average particle size of the second active particles is Dv250, then 0.07≤Dv250 / Dv150≤0.4.
[0008] Furthermore, the average particle size of the first active particles is Dv150, and the average particle size of the first solid electrolyte is Dv350, then 0.1≤Dv350 / Dv150≤0.5.
[0009] Furthermore, the average particle size Dv150 of the first active particles is in the range of 1 μm ≤ Dv150 ≤ 3 μm; the average particle size Dv250 of the second active particles is in the range of 0.2 μm ≤ Dv250 ≤ 0.5 μm; the average particle size Dv350 of the first solid electrolyte is in the range of 0.3 μm ≤ Dv350 ≤ 0.6 μm.
[0010] Furthermore, the gram capacity of the first active particles is greater than the gram capacity of the second active particles, the first active particles include ternary material particles, and the second active particles include lithium manganese iron phosphate particles.
[0011] Furthermore, the chemical formula of the ternary material particles includes LiNi x Co y Mn 1-x-y O2, wherein x ranges from 0.6 to 0.9 and y ranges from 0.05 to 0.35.
[0012] Furthermore, the active core also includes a first binder, and the active core includes, by mass fraction, 55% to 65% of the first active particles, 20% to 30% of the second active particles, 5% to 10% of the first solid electrolyte and 5% to 10% of the first binder.
[0013] Furthermore, the first solid electrolyte includes at least one of an oxide solid electrolyte and a sulfide solid electrolyte; the oxide solid electrolyte includes Li 1.3 Al 0.3 Ti 1.7 (PO4)3; the sulfide solid electrolyte includes at least one of Li2S-P2S5, Li2S-SiS2-P2S5-LiI.
[0014] Furthermore, the adhesion layer includes, by mass fraction, 60% to 80% of third active particles, 10% to 35% of a second solid electrolyte, and 5% to 10% of a second binder.
[0015] Furthermore, the third active particles include lithium iron manganese phosphate particles, the second solid electrolyte includes at least one of an oxide solid electrolyte and a sulfide solid electrolyte; the oxide solid electrolyte includes Li 1.3 Al 0.3 Ti 1.7 (PO4)3; the sulfide solid electrolyte includes at least one of Li2S-P2S5, Li2S-SiS2-P2S5-LiI.
[0016] Furthermore, the thickness h1 of the adhesion layer is in the range of 0.5 μm≤h1≤0.8 μm.
[0017] Furthermore, the coating layer comprises 5% to 10% of the third solid electrolyte and 90% to 95% of the conductive polymer by mass.
[0018] Furthermore, the third solid electrolyte includes at least one of an oxide solid electrolyte and a sulfide solid electrolyte; the oxide solid electrolyte includes Li 1.3 Al 0.3 Ti 1.7(PO4)3; the sulfide solid electrolyte includes at least one of Li2S-P2S5, Li2S-SiS2-P2S5-LiI; the conductive polymer includes at least one of polypyrrole, polyaniline, and polyacetylene.
[0019] Furthermore, the thickness h2 of the coating layer is in the range of 1 μm≤h2≤3 μm.
[0020] Furthermore, the average particle size Dv50 of the positive electrode active particles is in the range of 5 μm≤Dv50≤8 μm.
[0021] In a second aspect, the present application also provides a positive electrode sheet, which includes:
[0022] a positive electrode current collector; and
[0023] A positive electrode active layer, wherein the positive electrode active layer is disposed on the surface of the positive electrode current collector, and the positive electrode active layer comprises the positive electrode active particles described in the first aspect of the present application.
[0024] In a third aspect, an embodiment of the present application further provides a solid-state battery, characterized in that it comprises: the positive electrode plate, the solid electrolyte layer and the negative electrode plate described in the second aspect of the present application; the solid electrolyte layer is located between the positive electrode plate and the negative electrode plate.
[0025] The positive active particles of the embodiment of the present application include an active core, an adhesion layer and a coating layer. The active core includes a first active particle and a second active particle, and the average particle size of the first active particle is greater than the average particle size of the second active particle, so that the second active particle in the active core can be better adsorbed on the surface of the first active particle and fill the gap after the accumulation of multiple first active particles, thereby increasing the contact area between the multiple first active particles, which is conducive to the transmission of ions and electrons, and improving the ionic conductivity and electronic conductivity of the positive active particles. When the positive active particles are applied to solid-state batteries, the kinetic performance of the solid-state battery can be improved; and filling the second active particles in the gaps where multiple first active particles are accumulated can improve the energy density of the positive active particles. In addition, the active core also includes a first solid electrolyte, and the average particle size of the first active particle is greater than the average particle size of the first solid electrolyte, which allows the first solid electrolyte to be well adsorbed on the surface of the first active particle and fill the gaps generated by the accumulation of the first active particles. The first solid electrolyte acts as a diffusion network for ions (such as lithium ions), which can improve the transmission rate of ions, reduce impedance, and improve the kinetic performance of the solid-state battery using the positive active particles. Furthermore, the adhesion layer is wrapped around the surface of the active core. The adhesion layer can not only reduce the internal stress transmission in the particles of the active core and play a buffering role, but also facilitate a more uniform coating of the coating layer. The adhesion layer can better build a network of electronic conduction and ion transport connecting the active core and the coating layer, so that the positive electrode active particles have higher electrochemical performance. Furthermore, during the charge and discharge process of the positive electrode active particles, Li + Continuous release and embedding will lead to internal stress concentration of the positive electrode active particles, which may cause the positive electrode active particles to break. In the present embodiment, the coating layer is wrapped around the surface of the adhesion layer, and the coating layer can restrain the active core and the adhesion layer, thereby improving the overall mechanical strength of the positive electrode active particles, thereby inhibiting the breakage of the positive electrode active particles and improving the cycle capacity retention rate of the solid-state battery using the positive electrode active particles. Moreover, the coating layer can also increase the ion transfer rate, reduce the interface impedance, and improve the kinetic performance of the solid-state battery using the positive electrode active particles. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0027] Figure 1 Schematic diagram of the structure of positive electrode active particles according to an embodiment of the present application.
[0028] Figure 2It is a schematic diagram of the structure of positive electrode active particles in another embodiment of the present application.
[0029] Figure 3 It is a schematic diagram of a process for preparing positive electrode active particles according to an embodiment of the present application.
[0030] Figure 4 It is a schematic diagram of the structure of the positive electrode plate of one embodiment of the present application.
[0031] Figure 5 It is a schematic diagram of the structure of a solid-state battery according to an embodiment of the present application.
[0032] Figure 6 A solid-state battery according to an embodiment of the present application Figure 5 Schematic diagram of the cross-sectional structure in the AA direction.
[0033] Figure 7 This is a scanning electron microscope image of the lithium manganese iron phosphate of Example 1 of the present application.
[0034] Figure 8 This is a scanning electron microscope image of the ternary material particles of Example 1 of the present application.
[0035] Fig. 9 This is a scanning electron microscope image of the intermediate powder of Example 1 of the present application.
[0036] Fig.10 This is a particle size distribution diagram of lithium manganese iron phosphate, ternary material particles and positive electrode active particles in Example 1 of the present application.
[0037] Fig.11 This is a scanning electron microscope image of the cross section of the positive electrode sheet of Comparative Example 1 of the present application.
[0038] Description of reference numerals:
[0039] 100 - positive electrode active particles, 10 - active core, 20 - attachment layer, 30 - coating layer, 200 - positive electrode plate, 210 - positive electrode current collector, 220 - positive electrode active layer, 300 - solid-state battery, 310 - solid electrolyte layer, 320 - negative electrode plate, 330 - shell, 331 - accommodating cavity. DETAILED DESCRIPTION
[0040] In order to enable those skilled in the art to better understand the solution of the present application, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.
[0041] The terms "first", "second", etc. in the specification and claims of this application and the above-mentioned drawings are used to distinguish different objects, rather than to describe a specific order. In addition, the terms "including" and "having" and any variations thereof are intended to cover non-exclusive inclusions. For example, a process, method, system, product or device that includes a series of steps or units is not limited to the listed steps or units, but optionally includes steps or units that are not listed, or optionally includes other steps or units inherent to these processes, methods, products or devices.
[0042] The technical solutions in the embodiments of the present application will be described below in conjunction with the accompanying drawings.
[0043] It should be noted that, for the convenience of explanation, in the embodiments of the present application, the same figure marks represent the same components, and for the sake of brevity, detailed descriptions of the same components are omitted in different embodiments.
[0044] At present, the generation of green electricity generally relies on photovoltaics, wind power, and hydropower, etc. However, wind and solar energy generally have problems of strong intermittency and large volatility, which will cause instability in the power grid, insufficient electricity during peak hours, and too much electricity during valley hours. Unstable voltage will also cause damage to electricity. Therefore, insufficient electricity demand or insufficient grid acceptance capacity may cause the problem of "abandoning wind and solar power". To solve these problems, we must rely on energy storage. That is, converting electrical energy into other forms of energy through physical or chemical means and storing it, and converting energy into electrical energy and releasing it when needed. In simple terms, energy storage is like a large "power bank". When photovoltaic and wind energy are sufficient, electrical energy is stored and the stored electricity is released when needed.
[0045] Energy storage is inseparable from batteries, which include liquid batteries and solid-state batteries. As liquid batteries, lithium-ion batteries have high energy density and service life, so they are widely used. However, liquid batteries are prone to explosion and are less safe than solid-state batteries.
[0046] As a new type of battery technology, solid-state batteries have broad development prospects and market demand. In the future, with the continuous advancement of technology and the increase in market demand, solid-state batteries are expected to be widely used and become one of the important development directions in the field of energy storage. Since all-solid-state batteries use solid electrolytes to replace all liquid electrolytes, their ionic conductivity and electronic conductivity are significantly reduced, which reduces the electrical performance of solid-state batteries.
[0047] See also Figure 1 and Figure 2The embodiment of the present application provides a positive electrode active particle 100, which includes an active core 10, an adhesion layer 20 and a coating layer 30. The active core 10 includes a first active particle, a second active particle and a first solid electrolyte, the average particle size of the first active particle is greater than the average particle size of the first solid electrolyte, and the average particle size of the first solid electrolyte is greater than the average particle size of the second active particle; the adhesion layer 20 is wrapped on the surface of the active core 10; the coating layer 30 is wrapped on the surface of the adhesion layer 20.
[0048] The positive electrode active particles 100 of the embodiment of the present application are applied to a solid-state battery as a main component of a positive electrode active layer of a positive electrode sheet of the solid-state battery.
[0049] It should be noted that the positive electrode active particle 100 is a core-shell structure, and the adhesion layer 20 and the coating layer 30 are sequentially wrapped on the surface of the active core 10. In other words, the adhesion layer 20 wraps the active core 10 inside it, and the coating layer 30 wraps the active core 10 and the adhesion layer 20 inside it.
[0050] It can be understood that the first active particles are particles that can be used as positive electrode active materials. The second active particles are particles that can be used as positive electrode active materials.
[0051] It should be noted that the active core 10 is composed of first active particles, second active particles and a first solid electrolyte. Since the average particle size of the first active particles is larger than the average particle size of the first solid electrolyte, and the average particle size of the first solid electrolyte is larger than the average particle size of the second active particles, the first solid electrolyte and the second active particles can fill the pores left by the accumulation of the first active particles, so that the first active particles, the second active particles and the first solid electrolyte in the active core 10 are easier to be more tightly arranged, thereby increasing the contact area between adjacent first active particles in the active core 10.
[0052] Optionally, the adhesion layer 20 has ion conductivity and electrical conductivity, that is, the adhesion layer 20 can perform ion transmission and electron transmission.
[0053] Optionally, the coating layer 30 has ion conductivity and electrical conductivity, that is, the coating layer 30 can perform ion transmission and electron transmission.
[0054] The positive electrode active particle 100 of the embodiment of the present application includes an active core 10, an adhesion layer 20 and a coating layer 30. The active core 10 includes a first active particle and a second active particle, and the average particle size of the first active particle is greater than the average particle size of the second active particle, so that the second active particle in the active core 10 can be better adsorbed on the surface of the first active particle and fill the gap after the accumulation of multiple first active particles, thereby increasing the contact area between the multiple first active particles, facilitating the transmission of ions and electrons, and improving the ionic conductivity and electronic conductivity of the positive electrode active particle 100. When the positive electrode active particle 100 is applied to a solid-state battery, the kinetic performance of the solid-state battery can be improved; moreover, filling the second active particle in the gap between the accumulation of multiple first active particles can improve the energy density of the positive electrode active particle 100. In addition, the active core 10 also includes a first solid electrolyte. The average particle size of the first active particles is larger than the average particle size of the first solid electrolyte. This allows the first solid electrolyte to be well adsorbed on the surface of the first active particles and fill the gaps generated by the accumulation of the first active particles. The first solid electrolyte acts as a diffusion network for ions (such as lithium ions), which can increase the ion transmission rate, reduce impedance, and improve the kinetic performance of the solid-state battery using the positive electrode active particles 100. Furthermore, the adhesion layer 20 is wrapped around the surface of the active core 10. The adhesion layer 20 can not only reduce the internal stress transmission in the particles of the active core 10 and play a buffering role, but also facilitates a more uniform coating of the coating layer 30. The adhesion layer 20 can better construct a network of electronic conduction and ion transmission connecting the active core 10 and the coating layer 30, so as to enable the positive electrode active particles 100 to have higher electrochemical performance. Furthermore, during the charge and discharge process of the positive electrode active particles 100, Li + Continuous release and embedding will lead to internal stress concentration of the positive electrode active particles 100, which may cause the positive electrode active particles 100 to break. In the present embodiment, the coating layer 30 is wrapped around the surface of the adhesion layer 20. The coating layer 30 can restrain the active core 10 and the adhesion layer 20, thereby improving the overall mechanical strength of the positive electrode active particles 100, thereby inhibiting the breakage of the positive electrode active particles 100 and improving the cycle capacity retention rate of the solid-state battery using the positive electrode active particles 100. In addition, the coating layer 30 can also increase the ion transfer rate, reduce the interface impedance, and improve the kinetic performance of the solid-state battery using the positive electrode active particles 100.
[0055] In some embodiments, the average particle size of the first active particles is Dv150, and the average particle size of the second active particles is Dv250, then 0.07≤Dv250 / Dv150≤0.4.
[0056] The term "Dv150" is the volume average particle size of the first active particles, and refers to the particle size value at which powder particles smaller than and larger than the particle size each account for 50% in the powder particle size distribution.
[0057] The term "Dv250" is the volume average particle size of the second active particles, and refers to the particle size value at which powder particles smaller than and larger than the particle size each account for 50% in the powder particle size distribution.
[0058] It can be understood that the ratio of the average particle size Dv250 of the second active particles to the average particle size Dv150 of the first active particles ranges from 0.07 to 0.4.
[0059] Specifically, Dv250 / Dv150 may be, but is not limited to, 0.07, 0.08, 0.1, 0.13, 0.15, 0.18, 0.2, 0.23, 0.25, 0.28, 0.3, 0.33, 0.35, 0.38, 0.4, etc.
[0060] In this embodiment, Dv250 / Dv150 is too small, which may be due to Dv250 being too small or Dv150 being too large. When Dv250 is too small, the second active particles are prone to agglomeration, resulting in poor and uneven adsorption of the second active particles on the first active particles, thereby reducing the electronic conductivity of the active core 10. When Dv150 is too large, the contact area between the first active particles is small, and the gaps between the first active particles are too large to be filled, resulting in poor contact and reducing the kinetic performance of the solid-state battery. In addition, the lithium insertion distance of lithium ions is lengthened, thereby reducing the kinetic performance of the solid-state battery. Furthermore, Dv250 being too small or Dv150 being too large reduces the compactness of the stacking of the first active particles and the second active particles, thereby easily resulting in poor contact between adjacent first active particles and reducing the electronic conductivity and ionic conductivity of the positive electrode active particles 100.
[0061] In this embodiment, if Dv250 / Dv150 is too large, it may be that Dv250 is too large, or Dv150 is too small. When Dv250 is too large, the impedance of the second active particle is increased, and the ionic conductivity and lithium ion diffusion coefficient of the second active particle are reduced; when Dv150 is too small, it is easy to cause the adhesion layer 20 to fail to adhere, the adhesion layer 20 is unevenly coated, the shape of the active core 10 is uneven, gaps are generated, and the sphericity is low, which makes the positive electrode active particles 100 easy to break, and the cycle capacity retention rate of the positive electrode active particles 100 is reduced; in addition, Dv250 is too large or Dv150 is too small, which reduces the compactness of the stacking of the first active particles and the second active particles, and easily leads to poor contact between adjacent first active particles, thereby reducing the electronic conductivity and ionic conductivity of the positive electrode active particles 100.
[0062] Furthermore, 0.1≤Dv250 / Dv150≤0.2, so that the positive electrode active particles 100 have higher ionic conductivity and electronic conductivity, so that the solid-state battery using the positive electrode active particles 100 has better kinetic performance and higher cycle capacity retention rate.
[0063] In some embodiments, the average particle size of the first active particles is Dv150, and the average particle size of the first solid electrolyte is Dv350, then 0.1≤Dv350 / Dv150≤0.5.
[0064] The term “Dv350” is the volume average particle size of the first solid electrolyte, and refers to a particle size value at which powder particles smaller than and larger than this particle size each account for 50% in the powder particle size distribution.
[0065] It can be understood that the ratio of the average particle size Dv350 of the first solid electrolyte to the average particle size Dv150 of the first active particles ranges from 0.1 to 0.5.
[0066] Specifically, Dv350 / Dv150 can be, but is not limited to, 0.1, 0.13, 0.15, 0.18, 0.2, 0.23, 0.25, 0.28, 0.3, 0.33, 0.35, 0.38, 0.4, 0.43, 0.45, 0.48, 0.5, etc.
[0067] In this embodiment, Dv350 / Dv150 is too small, which may be due to Dv350 being too small or Dv150 being too large. When Dv350 is too small, the difficulty of preparing the first solid electrolyte is increased, and the cost of the first solid electrolyte is increased; when Dv150 is too large, the contact area between the first active particles is small, and the gaps between the first active particles are too large, making them difficult to fill and prone to poor contact, thereby reducing the kinetic performance of the solid-state battery; in addition, the lithium insertion distance of lithium ions is lengthened, thereby reducing the kinetic performance of the solid-state battery; furthermore, Dv350 being too small or Dv150 being too large reduces the compactness of the stacking of the first active particles and the second active particles, easily leading to poor contact between adjacent first active particles, thereby reducing the electronic conductivity and ionic conductivity of the positive electrode active particles 100.
[0068] In this embodiment, if Dv350 / Dv150 is too large, it may be that Dv350 is too large, or Dv150 is too small. When Dv350 is too large, the diffusion path of ions in the positive electrode active particles 100 becomes longer, the diffusion speed is reduced, and the kinetic performance of the solid-state battery using the positive electrode active particles 100 is reduced; when Dv150 is too small, it is easy to cause the adhesion layer 20 to fail to adhere, the adhesion layer 20 is unevenly coated, the shape of the active core 10 is uneven, gaps are generated, and the sphericity is low, making the positive electrode active particles 100 easy to break, reducing the cycle capacity retention rate of the positive electrode active particles 100; in addition, Dv350 is too large or Dv150 is too small, which reduces the compactness of the stacking of the first active particles and the second active particles, easily leading to poor contact between adjacent first active particles, and reducing the electronic conductivity and ionic conductivity of the positive electrode active particles 100.
[0069] Furthermore, 0.13≤Dv350 / Dv150≤0.25. This allows the positive electrode active particles 100 to have higher ionic conductivity and electronic conductivity, thereby allowing the solid-state battery using the positive electrode active particles 100 to have better kinetic performance and higher cycle capacity retention rate.
[0070] In some embodiments, the average particle size Dv150 of the first active particles is in the range of 1 μm≤Dv150≤3 μm.
[0071] Specifically, the average particle size Dv150 of the first active particles may be, but is not limited to, 1.0 μm, 1.2 μm, 1.4 μm, 1.6 μm, 1.8 μm, 2.0 μm, 2.2 μm, 2.4 μm, 2.6 μm, 2.8 μm, 3 μm, etc.
[0072] In this embodiment, the average particle size Dv150 of the first active particles is too small, which may cause the adhesion layer 20 to be unable to adhere, the adhesion layer 20 to be unevenly coated, the shape of the active core 10 to be uneven, and gaps to be generated. The sphericity is low, which makes the positive electrode active particles 100 easy to break, thereby reducing the cycle capacity retention rate of the positive electrode active particles 100; if the average particle size Dv150 of the first active particles is too large, the contact area between the first active particles is small, and the gaps between the first active particles are too large to be easily filled, and poor contact is easily caused, thereby reducing the kinetic performance of the solid-state battery; in addition, the lithium insertion distance of lithium ions is lengthened, thereby reducing the kinetic performance of the solid-state battery.
[0073] Optionally, the range of the average particle size Dv250 of the second active particles is: 0.2 μm≤Dv250≤0.5 μm.
[0074] Specifically, the average particle size Dv250 of the second active particles may be, but is not limited to, 0.2 μm, 0.25 μm, 0.3 μm, 0.35 μm, 0.4 μm, 0.45 μm, 0.5 μm, etc.
[0075] In this embodiment, if the average particle size Dv250 of the second active particles is too small, the second active particles are prone to agglomeration, resulting in poor and uneven adsorption of the second active particles on the first active particles, thereby reducing the electronic conductivity of the active core 10; if the average particle size Dv250 of the second active particles is too large, the impedance of the second active particles is increased, thereby reducing the ionic conductivity and lithium ion diffusion coefficient of the second active particles.
[0076] Optionally, the range of the average particle size Dv350 of the first solid electrolyte is: 0.3 μm≤Dv350≤0.6 μm.
[0077] Specifically, the average particle size Dv350 of the first solid electrolyte may be, but is not limited to, 0.3 μm, 0.35 μm, 0.4 μm, 0.45 μm, 0.5 μm, 0.55 μm, 0.6 μm, etc.
[0078] In this embodiment, if the average particle size Dv350 of the first solid electrolyte is too small, the difficulty of preparing the first solid electrolyte is increased and the cost of the first solid electrolyte is increased; if the average particle size Dv350 of the first solid electrolyte is too large, the diffusion path of ions in the positive electrode active particles 100 becomes longer, the diffusion rate decreases, and the kinetic performance of the solid-state battery using the positive electrode active particles 100 is reduced.
[0079] In some embodiments, the gram capacity of the first active particles is greater than the gram capacity of the second active particles, the first active particles include ternary material particles, and the second active particles include lithium manganese iron phosphate particles.
[0080] In this embodiment, the gram capacity of the first active particles with a larger average particle size is greater than the gram capacity of the second active particles with a smaller average particle size, so that the gram capacity of the positive electrode active particles 100 can be better improved. In addition, the first active particles include ternary material particles, and the second active particles include lithium iron manganese phosphate particles. These materials have a higher gram capacity, which can better improve the capacity of the positive electrode active particles 100. In addition, the surface of the lithium iron manganese phosphate particles has a self-contained conductive carbon layer, so that the electronic conductivity of the active core 10 can be better improved, and the kinetic performance of the positive electrode active particles 100 can be improved.
[0081] In some embodiments, the chemical formula of the ternary material particles includes LiNi x Coy Mn 1-x-y O2, wherein x ranges from 0.6 to 0.9 and y ranges from 0.05 to 0.35.
[0082] Specifically, x may be, but is not limited to, 0.6, 0.65, 0.7, 0.75, 0.8, 0.85, 0.9, etc. If x is too small, the Ni content in the ternary material particles is too small, which reduces the gram capacity of the ternary material particles; if x is too large, the Ni content in the ternary material particles is too large, and the first active particles change too much in volume during the charge and discharge cycle, and the internal stress is too large, making the positive active particles 100 easy to break, reducing the cycle capacity retention rate of the solid-state battery using the positive active particles 100.
[0083] Specifically, y may be, but is not limited to, 0.05, 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, etc. If y is too small, the Ni content in the ternary material particles is too high, and the volume change of the first active particles during the charge and discharge cycle is too large, and the internal stress is too large, so that the positive electrode active particles 100 are easy to break, and the cycle capacity retention rate of the solid-state battery using the positive electrode active particles 100 is reduced; if y is too large, the Ni content in the ternary material particles is too low, and the gram capacity of the ternary material particles is reduced.
[0084] In a specific embodiment, x is 0.6, y is 0.2, that is, the ternary material particles are LiNi 0.6 Co 0.2 Mn 0.2 O2.
[0085] In this embodiment, by selecting the composition and ratio of the ternary material particles, the positive electrode active particles 100 have a higher gram capacity and a higher cycle capacity retention rate.
[0086] In some embodiments, the active core 10 further includes a first binder, and the active core 10 includes, by mass fraction, 55% to 65% of the first active particles, 20% to 30% of the second active particles, 5% to 10% of the first solid electrolyte, and 5% to 10% of the first binder.
[0087] Specifically, the mass fraction of the first active particles in the active core 10 can be but is not limited to 55%, 56%, 57%, 58%, 59%, 60%, 61%, 62%, 63%, 64%, 65%, etc. If the mass fraction of the first active particles in the active core 10 is too small, the gram capacity of the positive electrode active particles 100 is reduced. In addition, the adhesion effect of the second active particles on the first active particles is reduced, so that the active core 10 is prone to have gaps and the sphericity is reduced, which makes the positive electrode active particles 100 easy to break, thereby reducing the cycle capacity retention rate of the positive electrode active particles 100; if the mass fraction of the first active particles in the active core 10 is too large, the total capacity in the active particles will increase. However, when the mass fraction of the first active particles is too large, the content of the second active particles and the first solid electrolyte is reduced, which makes it impossible to fully fill and stack the second active particles with the first active particles, reducing the contact area between the first active particles and the thickness of the adhesion layer 20, thereby reducing the electronic conductivity of the positive electrode active particles 100 and the buffering effect of the adhesion layer 20, which in turn reduces the gram capacity of the positive electrode active particles 100 and the cycle capacity retention rate.
[0088] Specifically, the mass fraction of the second active particles in the active core 10 may be, but is not limited to, 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 30%, etc. The second active particles can allow adjacent first active particles to have a larger contact area, thereby allowing the positive electrode active particles 100 to have a higher electronic conductivity. Therefore, when the content of the second active particles in the active core 10 is too little, the gaps between the first active particles are insufficiently filled, and the improvement of the ion conductivity of the positive electrode active particles 100 is limited; the gram capacity of the second active particles is lower than the gram capacity of the first active particles. When the content of the second active particles in the active core 10 is too much, the capacity of the positive electrode active particles 100 will be reduced.
[0089] Specifically, the mass fraction of the first solid electrolyte in the active core 10 may be, but is not limited to, 5%, 6%, 7%, 8%, 9%, 10%, etc. The first solid electrolyte, as an ion diffusion network, can increase the ion diffusion rate of the active core 10 and improve the kinetic performance of the positive electrode active particles 100. When the content of the first solid electrolyte in the active core 10 is too small, the conductive network of the active core 10 is not fully constructed, which reduces the ion transmission capacity of the active core 10; when the content of the first solid electrolyte in the active core 10 is too large, the content of the first active particles is reduced, which reduces the gram capacity of the positive electrode active particles 100.
[0090] Specifically, the mass fraction of the first binder in the active core 10 may be, but is not limited to, 5%, 6%, 7%, 8%, 9%, 10%, etc. If the mass fraction of the first binder in the active core 10 is too low, the active core 10 is easily broken or disintegrated; if the mass fraction of the first binder in the active core 10 is too high, the ionic conductivity and electronic conductivity of the active core 10 are reduced because the first binder is not conductive and does not contain ions. In addition, the proportion of the first active particles is reduced, thereby reducing the gram capacity of the positive electrode active particles 100.
[0091] Optionally, the first binder may be, but is not limited to, at least one of polyvinylidene fluoride (PVDF), polyamide (PA), polyacrylonitrile (PAN), polyacrylate, polyvinylether, polymethylmethacrylate (PMMA), polyhexafluoropropylene, etc.
[0092] In this embodiment, the composition and proportion of the active core 10 are controlled so that the positive electrode active particles 100 have a higher gram capacity and a higher cycle capacity retention rate.
[0093] In some embodiments, the first solid electrolyte includes at least one of an oxide solid electrolyte and a sulfide solid electrolyte; the oxide solid electrolyte includes Li 1.3 Al 0.3 Ti 1.7( PO4)3; the sulfide solid electrolyte includes at least one of Li2S-P2S5, Li2S-SiS2-P2S5-LiI.
[0094] In this embodiment, the use of these solid electrolytes can better construct the ion diffusion network of the active core 10 , can better accelerate the diffusion rate of ions, reduce interface impedance, and improve the kinetic performance of the positive electrode active particles 100 .
[0095] In some embodiments, the adhesion layer 20 includes 60% to 80% by mass of the third active particles, 10% to 35% by mass of the second solid electrolyte, and 5% to 10% by mass of the second binder.
[0096] Specifically, the mass fraction of the third active particles in the attachment layer 20 may be, but is not limited to, 60%, 63%, 65%, 68%, 70%, 73%, 75%, 78%, 80%, etc. The third active particles may be used as active materials, and may also improve electronic conductivity. If the mass fraction of the third active particles in the attachment layer 20 is too low, the gram capacity of the positive electrode active particles 100 is reduced and the electronic conductivity of the attachment layer 20 is reduced; if the mass fraction of the third active particles in the attachment layer 20 is too high, the content of the second solid electrolyte is reduced, and the ionic conductivity of the attachment layer 20 is reduced.
[0097] Specifically, the mass fraction of the second solid electrolyte in the attachment layer 20 may be, but is not limited to, 10%, 15%, 20%, 25%, 30%, 35%, etc. The second solid electrolyte constructs an ion diffusion network, which can better accelerate the diffusion rate of ions, reduce interface impedance, and improve the kinetic performance of the positive electrode active particles 100. If the mass fraction of the second solid electrolyte in the attachment layer 20 is too low, the ionic conductivity of the attachment layer 20 is reduced; if the mass fraction of the second solid electrolyte in the attachment layer 20 is too high, the content of the third active particles is reduced, and the gram capacity of the positive electrode active particles 100 is reduced.
[0098] Specifically, the mass fraction of the second binder in the attachment layer 20 may be, but is not limited to, 5%, 6%, 7%, 8%, 9%, 10%, etc. If the mass fraction of the second binder in the attachment layer 20 is too low, the attachment layer 20 is easily broken or disintegrated; if the mass fraction of the second binder in the attachment layer 20 is too high, the ionic conductivity and electronic conductivity of the attachment layer 20 are reduced because the second binder is not conductive and does not receive ions. In addition, the proportion of the third active particles is reduced, thereby reducing the gram capacity of the positive electrode active particles 100.
[0099] Optionally, the third active particle is different from the first active particle, and the third active particle can be the same as or different from the second active particle. When the third active particle is the same as the second active particle, the preparation process of the positive electrode active particle 100 can be simplified.
[0100] Optionally, the second solid electrolyte may be the same as or different from the first solid electrolyte. When the second solid electrolyte is the same as the first solid electrolyte, the preparation process of the positive electrode solid electrolyte can be better simplified.
[0101] Optionally, the second binder may be, but is not limited to, at least one of polyvinylidene fluoride, polyamide, polyacrylonitrile, polyacrylate, polyvinyl ether, polymethyl methacrylate, polyhexafluoropropylene, and the like.
[0102] Optionally, the second binder may be the same as or different from the first binder. When the second binder is the same as the first binder, the preparation process of the positive electrode binder may be simplified.
[0103] In some embodiments, the third active particles include lithium manganese iron phosphate particles (such as LiMn 0.6 Fe 0.4 PO4), the second solid electrolyte includes at least one of an oxide solid electrolyte and a sulfide solid electrolyte; the oxide solid electrolyte includes Li 1.3 Al 0.3 Ti 1.7 (PO4)3; the sulfide solid electrolyte includes at least one of Li2S-P2S5, Li2S-SiS2-P2S5-LiI.
[0104] In this embodiment, the third active particles include lithium iron manganese phosphate particles, and the surface of the lithium iron manganese phosphate particles has a self-contained conductive carbon layer, so that the electronic conductivity of the adhesion layer 20 can be better improved, and the dynamic performance of the positive electrode active particles 100 can be improved. In addition, the second solid electrolyte includes at least one of an oxide solid electrolyte and a sulfide solid electrolyte; the oxide solid electrolyte includes Li 1.3 Al 0.3 Ti 1.7 (PO4)3; the sulfide solid electrolyte includes at least one of Li2S-P2S5, Li2S-SiS2-P2S5-LiI. The use of these solid electrolytes can better construct the ion diffusion network of the active core 10, which can better accelerate the diffusion rate of ions, reduce interface impedance, and improve the kinetic performance of the positive electrode active particles 100.
[0105] In some embodiments, the thickness h1 of the adhesion layer 20 is in the range of 0.5 μm≤h1≤0.8 μm.
[0106] Specifically, the thickness h1 of the adhesion layer 20 may be, but is not limited to, 0.5 μm, 0.55 μm, 0.6 μm, 0.65 μm, 0.7 μm, 0.75 μm, 0.5 μm, etc.
[0107] In the present embodiment, if the thickness h1 of the adhesion layer 20 is too thin, the buffering effect of the adhesion layer 20 on the internal stress of the positive electrode active particles 100 is reduced, or even fails to play the role of buffering the internal stress. In addition, the adhesion layer 20 may be incompletely coated on the active core 10 or have gaps, so that the electron transmission channel and the ion transmission network between the active core 10 and the coating layer 30 are incompletely constructed, thereby reducing the ionic conductivity and electronic conductivity of the positive electrode active particles 100, thereby reducing the kinetic performance of the positive electrode active particles 100; if the thickness h1 of the adhesion layer 20 is too thick, the proportion of active substances in the positive electrode active particles 100 is reduced, thereby reducing the gram capacity of the positive electrode active particles 100.
[0108] In some embodiments, the coating layer 30 includes 5% to 10% by mass of the third solid electrolyte and 90% to 95% by mass of the conductive polymer.
[0109] Specifically, the mass fraction of the third solid electrolyte in the coating layer 30 may be, but is not limited to, 10%, 15%, 20%, 25%, 30%, 35%, etc. The third solid electrolyte constructs an ion diffusion network, which can better accelerate the diffusion speed of ions, reduce the interface impedance, and improve the kinetic performance of the positive electrode active particles 100. If the mass fraction of the third solid electrolyte in the coating layer 30 is too low, the ionic conductivity of the coating layer 30 is reduced, and the kinetic performance of the positive electrode active particles 100 is reduced; if the mass fraction of the third solid electrolyte in the coating layer 30 is too high, the content of the conductive polymer in the coating layer 30 is reduced, and the binding effect of the coating layer 30 on the active core 10 and the adhesion layer 20 is reduced, so that the positive electrode active particles 100 are easily broken during repeated lithium insertion and delithiation, and the cycle capacity protection rate of the positive electrode active particles 100 is reduced.
[0110] Specifically, the mass fraction of the conductive polymer in the coating layer 30 may be, but is not limited to, 90%, 91%, 923%, 93%, 94%, 95%, etc. The conductive polymer is fibrous (i.e., has a long molecular chain), and the molecular chains of the conductive polymer are entangled with each other, forming a strong bond to the active core 10 and the adhesion layer 20, which can improve the mechanical strength of the positive electrode active particles 100 and better inhibit the breakage of the positive electrode active particles 100 during repeated charge and discharge; in addition, the conductive polymer can also serve as an electron transmission channel of the coating layer 30. If the mass fraction of the conductive polymer in the coating layer 30 is too low, the binding effect of the coating layer 30 on the active core 10 and the adhesion layer 20 is reduced, so that the positive electrode active particles 100 are easily broken during repeated lithium insertion and removal, thereby reducing the cycle capacity protection rate of the positive electrode active particles 100; if the mass fraction of the conductive polymer in the coating layer 30 is too high, the content of the third solid electrolyte in the coating layer 30 is reduced, so that the ionic conductivity of the coating layer 30 decreases, the ion diffusion rate decreases, the interface impedance increases, and the kinetic performance of the positive electrode active particles 100 is reduced.
[0111] In some embodiments, the third solid electrolyte includes at least one of an oxide solid electrolyte and a sulfide solid electrolyte; the oxide solid electrolyte includes Li 1.3 Al 0.3 Ti 1.7 (PO4)3; the sulfide solid electrolyte includes at least one of Li2S-P2S5, Li2S-SiS2-P2S5-LiI; the conductive polymer includes at least one of polypyrrole, polyaniline, and polyacetylene.
[0112] The third solid electrolyte of this embodiment includes at least one of an oxide solid electrolyte and a sulfide solid electrolyte; the oxide solid electrolyte includes Li 1.3 Al 0.3 Ti 1.7 (PO4)3; the sulfide solid electrolyte includes at least one of Li2S-P2S5 and Li2S-SiS2-P2S5-LiI. The use of these solid electrolytes can better construct the ion diffusion network of the active core 10, can better accelerate the diffusion rate of ions, reduce the interface impedance, and improve the dynamic performance of the positive electrode active particles 100. In addition, the conductive polymer of this embodiment includes at least one of polypyrrole, polyaniline, and polyacetylene. These conductive polymers have high conductivity and can better improve the electronic conductivity of the coating. In addition, these polymers can better bind the active core 10 and the adhesion layer 20, and better reduce the probability of the positive electrode active particles 100 being broken during the charge and discharge process.
[0113] In some embodiments, the thickness h2 of the coating layer 30 is in the range of 1 μm≤h2≤3 μm.
[0114] Specifically, the thickness h2 of the coating layer 30 is, but not limited to, 1.0 μm, 1.2 μm, 1.4 μm, 1.6 μm, 1.8 μm, 2.0 μm, 2.2 μm, 2.4 μm, 2.6 μm, 2.8 μm, 3 μm, etc.
[0115] In this embodiment, if the thickness h2 of the coating layer 30 is too thin, the binding force of the coating layer 30 on the active core 10 and the adhesion layer 20 is insufficient, so that the positive electrode active particles 100 are easily broken during repeated charge and discharge; if the thickness h2 of the coating layer 30 is too thick, the ion transmission path of the positive electrode active particles 100 becomes longer, the ion diffusion rate decreases, and the kinetic performance deteriorates during the charge and discharge process.
[0116] In some embodiments, the average particle size Dv50 of the positive electrode active particles 100 is in the range of 5 μm≤Dv50≤8 μm.
[0117] Specifically, the average particle size Dv50 of the positive electrode active particles 100 can be but is not limited to 5.0μm, 5.2μm, 5.4μm, 5.6μm, 5.8μm, 6.0μm, 6.2μm, 6.4μm, 6.6μm, 6.8μm, 7.0μm, 7.2μm, 7.4μm, 7.6μm, 7.8μm, 8μm, etc.
[0118] In this embodiment, if the average particle size Dv50 of the positive electrode active particles 100 is too small, structural defects are likely to exist inside the positive electrode active particles 100, such as incomplete coating of the adhesion layer 20, uneven distribution of the coating layer 30, etc., which makes the positive electrode active particles 100 easy to break during repeated charge and discharge; if the average particle size Dv50 of the positive electrode active particles 100 is too large, the diffusion path of the ions becomes longer, the diffusion rate of the ions is reduced, and the kinetic performance of the positive electrode active particles 100 is reduced.
[0119] The term “Dv50” is the volume average particle size of the positive electrode active particles 100 , and refers to the particle size value at which the powder particles smaller than and larger than the particle size each account for 50% in the powder particle size distribution.
[0120] See also Figure 3 The present application also provides a method for preparing positive electrode active particles 100, which includes:
[0121] S201, providing first active particles, second active particles, a first solid electrolyte, a second solid electrolyte, a first binder and a second binder, wherein the first solid electrolyte is the same as the second solid electrolyte, and the first binder is the same as the second binder;
[0122] For detailed descriptions of other aspects of the first active particles, the second active particles, the first solid electrolyte, the second solid electrolyte, the first binder and the second binder, please refer to the descriptions of the corresponding parts of the above embodiments, which will not be repeated here.
[0123] S202, mixing the second active particles, the first solid electrolyte and the first binder in an organic solvent, then adding the first active particles, and mixing them evenly to obtain a slurry;
[0124] Optionally, the organic solvent may be, but is not limited to, N-methylpyrrolidone or the like.
[0125] S203, spray drying the slurry to obtain an intermediate powder, wherein the intermediate powder includes an active core 10 and an adhesion layer 20, wherein the adhesion layer 20 is coated on the outer periphery of the active core 10; and
[0126] Optionally, the feed rate of spray drying ranges from 5 mL / min to 15 mL / min. Specifically, the feed rate of spray drying can be, but is not limited to, 5 mL / min, 6 mL / min, 8 mL / min, 10 mL / min, 12 mL / min, 14 mL / min, 15 mL / min, etc. If the feed rate of spray drying is too slow, the particle size of the intermediate powder obtained is too large, so that the particle size of the positive active particles 100 obtained in the end is too large; if the feed rate of spray drying is too fast, the particle size of the intermediate powder obtained is too small, so that the particle size of the positive active particles 100 obtained in the end is too small.
[0127] Optionally, the spray drying temperature ranges from 180°C to 220°C. Specifically, the spray drying temperature may be, but is not limited to, 180°C, 185°C, 190°C, 195°C, 200°C, 205°C, 210°C, 205°C, 220°C, etc. If the spray drying temperature is too low, the particle size of the intermediate powder obtained is too large, so that the particle size of the positive active particles 100 obtained in the end is too large; if the spray drying temperature is too high, the particle size of the intermediate powder obtained is too small, so that the particle size of the positive active particles 100 obtained in the end is too small.
[0128] For detailed description of other aspects of the active core 10 and the adhesion layer 20 , please refer to the description of the corresponding parts of the above embodiments, which will not be repeated here.
[0129] S204 , forming a coating layer 30 on the surface of the intermediate powder to obtain positive electrode active particles 100 .
[0130] Optionally, the intermediate powder, the third solid electrolyte, and the monomer of the conductive polymer (such as pyrrole monomer) are mixed in a preset ratio, deionized water is added, and then a mixed solution is prepared by ultrasonic dispersion and magnetic stirring; a FeCl3·6H2O solution with a molar concentration of 0.8mol / L to 1mol / L (for example, 0.8mol / L, 0.9mol / L, 1mol / L) and a temperature of 10°C to 15°C (for example, 10°C, 13°C, 15°C, etc.) is prepared; then, according to the molar ratio of pyrrole monomer to FeCl3·6H2O in the mixed solution of 1:1, the FeCl3·6H2O solution is gradually added dropwise to the mixed solution, and the reaction temperature is controlled to be 2°C to 5°C (for example, 2°C, 3°C, 4°C, 5°C) to allow the solution to react fully; so as to form a coating layer 30 on the surface of the intermediate powder. After the reaction is completed, the product is washed and filtered with anhydrous ethanol and deionized water in succession until the washing liquid is clear and colorless. The product was then placed in a freeze dryer and cooled and dried at -50°C to obtain the positive electrode active particles 100.
[0131] Optionally, the monomer of the conductive polymer may be, but is not limited to, at least one of a pyrrole monomer, an aniline monomer, or an acetylene monomer.
[0132] See also Figure 4 The embodiment of the present application further provides a positive electrode plate 200, which includes a positive electrode collector 210 and a positive electrode active layer 220, wherein the positive electrode active layer 220 is disposed on the surface of the positive electrode collector 210, and the positive electrode active layer 220 includes the positive electrode active particles 100 described in the embodiment of the present application.
[0133] For detailed description of other aspects of the positive electrode active particles 100 , please refer to the description of the corresponding parts of the above embodiments, which will not be repeated here.
[0134] It can be understood that the positive electrode active layer 220 can cover one surface or two opposite surfaces of the positive electrode current collector 210 .
[0135] Optionally, the positive electrode current collector 210 may be, but is not limited to, an aluminum sheet or an aluminum foil.
[0136] Optionally, the positive electrode active layer 220 further includes a positive electrode conductor, a positive electrode binder and a fourth solid electrolyte.
[0137] Optionally, the positive electrode conductive agent may be, but is not limited to, at least one of conductive carbon black, acetylene black, carbon nanotubes, carbon fibers, graphene, and the like.
[0138] Optionally, the positive electrode binder may be but is not limited to at least one of polyvinylidene fluoride (PVDF), polyamide (PA), polyacrylonitrile (PAN), polyacrylate, polyvinylether, polymethyl methacrylate (PMMA), polyhexafluoropropylene, etc.
[0139] Optionally, the fourth solid electrolyte includes at least one of an oxide solid electrolyte and a sulfide solid electrolyte; the oxide solid electrolyte includes Li 1.3 Al 0.3 Ti 1.7 (PO4)3; the sulfide solid electrolyte includes at least one of Li2S-P2S5 and Li2S-SiS2-P2S5-LiI; the conductive polymer includes at least one of polypyrrole, polyaniline and polyacetylene. The use of these solid electrolytes can better construct the ion diffusion network of the active core 10, can better accelerate the diffusion speed of ions, reduce the interface impedance, and improve the dynamic performance of the positive electrode active particles 100.
[0140] It should be noted that the first solid electrolyte, the second solid electrolyte, the third solid electrolyte and the fourth solid electrolyte in the embodiment of the present application may be the same or different, or may be partially the same and partially different.
[0141] See also Figure 5 and Figure 6 The embodiment of the present application also provides a solid-state battery 300, which includes: the positive electrode plate 200, the solid electrolyte layer 310 and the negative electrode plate 320 described in the embodiment of the present application; the solid electrolyte layer 310 is located between the positive electrode plate 200 and the negative electrode plate 320, and is used to insulate the positive electrode plate 200 from the negative electrode plate 320 and transfer ions (such as lithium ions).
[0142] For detailed description of other aspects of the positive electrode plate 200 , please refer to the description of the corresponding parts of the above embodiment, which will not be repeated here.
[0143] It should be noted that the positive electrode sheet 200 , the solid electrolyte layer 310 and the negative electrode sheet 320 are stacked in sequence to form an electrode assembly.
[0144] Optionally, the solid electrolyte layer 310 includes a fifth solid electrolyte and a third binder. Optionally, the solid electrolyte layer 310 includes 90% to 96% of the fifth solid electrolyte and 4% to 10% of the third binder by mass fraction.
[0145] Optionally, the fifth solid electrolyte includes at least one of an oxide solid electrolyte and a sulfide solid electrolyte; the oxide solid electrolyte includes Li 1.3 Al 0.3 Ti 1.7 (PO4)3; the sulfide solid electrolyte includes at least one of Li2S-P2S5 and Li2S-SiS2-P2S5-LiI; the conductive polymer includes at least one of polypyrrole, polyaniline and polyacetylene. The use of these solid electrolytes can better construct the ion diffusion network of the active core 10, can better accelerate the diffusion speed of ions, reduce the interface impedance, and improve the dynamic performance of the positive electrode active particles 100.
[0146] Optionally, the third binder may be, but is not limited to, at least one of polyvinylidene fluoride, polyamide, polyacrylonitrile, polyacrylate, polyvinyl ether, polymethyl methacrylate, polyhexafluoropropylene, and the like.
[0147] Optionally, the negative electrode plate 320 may include but is not limited to at least one of a lithium plate, a lithium alloy plate, and the like.
[0148] Optionally, the solid-state battery 300 further includes a housing 330 , wherein the housing 330 has a receiving cavity 331 , and the receiving cavity 331 is used to receive the electrode assembly. That is, the housing 330 is used to receive the positive electrode sheet 200 , the solid electrolyte layer 310 , and the negative electrode sheet 320 .
[0149] The positive electrode active particles 100 and the solid-state battery 300 of the present application are further described below through specific embodiments.
[0150] Example 1
[0151] The method for preparing the solid-state battery 300 of this embodiment includes:
[0152] 1) Preparation of positive electrode active particles 100:
[0153] ① Lithium iron manganese phosphate material (LiMn 0.6 Fe 0.4 PO4, Dv250 particle size is 0.3μm, namely the second active particles and the third active particles), Li 1.3 Al 0.3 Ti 1.7(PO4)3 (first solid electrolyte and second solid electrolyte), polyvinylidene fluoride PVDF (first binder and second binder) are mixed evenly, N-methylpyrrolidone (NMP) is added as a solvent, stirred evenly, and then LiNi is gradually added. 0.6 Co 0.2 Mn 0.2 O2 (ternary material particles, i.e., the first active particles, Dv150 is 3 μm), and continue to stir evenly to obtain a uniformly mixed slurry; wherein, the ternary material particles, lithium manganese iron phosphate material, Li 1.3 Al 0.3 Ti 1.7 The mass ratio of (PO4)3 and PVDF is 55:30:10:5.
[0154] ② The slurry is spray-dried (feed rate is 10 mL / min, and the drying temperature is set to 200° C.) to form an intermediate powder with a certain particle size, wherein the intermediate powder includes an active core 10 and an adhesion layer 20 .
[0155] ③ The intermediate powder, Li 1.3 Al 0.3 Ti 1.7 (PO4)3 (i.e., the third solid electrolyte) and pyrrole monomer are mixed uniformly in a preset ratio, deionized water is added, and then a mixed solution is prepared by ultrasonic dispersion and magnetic stirring; a FeCl3·6H2O solution with a molar concentration of 0.9 mol / L and a temperature of 13°C is prepared, and then a FeCl3·6H2O solution with a molar concentration of 0.9 mol / L is gradually added dropwise to the mixed solution according to the molar ratio of pyrrole to FeCl3·6H2O in the mixed solution of 1:1, and the reaction temperature is controlled to be 4°C to allow the solution to fully react; after the reaction, the product is washed and filtered with anhydrous ethanol and deionized water in succession until the washing liquid is clear and colorless. Subsequently, the product is placed in a freeze dryer, and after cooling and drying at -50°C, the positive active particles 100 are obtained. The average particle size Dv50 of the positive active particles 100 is 8 μm, and the thickness h2 of the coating layer 30 (i.e., polypyrrole) of the positive active particles 100 measured by transmission electron microscopy is 1 μm.
[0156] The scanning electron microscope (SEM) image of the lithium manganese iron phosphate of this embodiment is as follows: Figure 7 The scanning electron microscope image of the ternary material particles of this embodiment is shown in Figure 8 The scanning electron microscope image of the intermediate powder of this embodiment is shown in Fig. 9 The particle size distribution of lithium manganese iron phosphate, ternary material particles, and positive electrode active particles 100 in this embodiment is shown in FIG. Fig.10 shown.
[0157] 2) Preparation of positive electrode sheet 200: Weigh positive electrode active particles 100, Li 1.3 Al 0.3 Ti 1.7 (PO4)3 (fourth solid electrolyte), graphene (positive electrode conductive agent), and PVDF (positive electrode binder) are mixed evenly in a stirring tank, and a solvent N-methylpyrrolidone (NMP) is added to obtain a uniform slurry, which is coated on a positive electrode current collector 210 aluminum foil, and vacuum dried in a vacuum drying oven at 150° C. for 15 h to obtain a positive electrode sheet 200;
[0158] Weigh Li according to the mass ratio of 95:5 1.3 Al 0.3 Ti 1.7 The (PO4)3 layer (fifth solid electrolyte) is mixed with PVDF binder and NMP to make a slurry, which is then coated on the positive electrode plate 200 and dried to obtain a stacked solid electrolyte layer 310 / positive electrode plate 200.
[0159] 3) Assembly of solid-state battery 300: Assemble in a glove box in the order of positive electrode shell, solid electrolyte layer 310 / positive electrode plate 200, lithium plate (negative electrode plate 320), stainless steel gasket, spring, and negative electrode shell, and place on a sealing machine to encapsulate to obtain a CR2032 button battery.
[0160] Example 2
[0161] The difference between this embodiment and embodiment 1 is that: in step ①, the ternary material particles, lithium manganese iron phosphate material, Li 1.3 Al 0.3 Ti 1.7 The mass ratio of (PO4)3 and PVDF is 60:25:10:5.
[0162] Example 3
[0163] The difference between this embodiment and embodiment 1 is that: in step ①, the ternary material particles, lithium manganese iron phosphate material, Li 1.3 Al 0.3 Ti 1.7 The mass ratio of (PO4)3 and PVDF is 65:20:10:5.
[0164] Example 4
[0165] The difference between this embodiment and embodiment 1 is that: in step ①, the ternary material particles, lithium manganese iron phosphate material, Li 1.3 Al 0.3 Ti 1.7 The mass ratio of (PO4)3 and PVDF is 70:15:10:5.
[0166] Example 5
[0167] The difference between this embodiment and embodiment 1 is that: in step ①, the ternary material particles, lithium manganese iron phosphate material, Li 1.3 Al 0.3 Ti 1.7 The mass ratio of (PO4)3 and PVDF is 55:30:7:8.
[0168] Example 6
[0169] The difference between this embodiment and embodiment 1 is that: in step ①, the ternary material particles, lithium manganese iron phosphate material, Li 1.3 Al 0.3 Ti 1.7 The mass ratio of (PO4)3 and PVDF is 55:30:5:10.
[0170] Example 7
[0171] The difference between this embodiment and embodiment 1 is that: in step ①, the ternary material particles, lithium manganese iron phosphate material, Li 1.3 Al 0.3 Ti 1.7 The mass ratio of (PO4)3 and PVDF is 55:30:3:12.
[0172] Example 8
[0173] The difference between this embodiment and embodiment 1 is that the average particle size Dv150 of the first active particles (ie, ternary material particles) of this embodiment is 2.5 μm.
[0174] Example 9
[0175] The difference between this embodiment and embodiment 1 is that the average particle size Dv150 of the first active particles (ie, ternary material particles) of this embodiment is 2.0 μm.
[0176] Example 10
[0177] The difference between this embodiment and embodiment 1 is that the average particle size Dv150 of the first active particles (ie, ternary material particles) of this embodiment is 1.5 μm.
[0178] Embodiment 11
[0179] The difference between this embodiment and embodiment 1 is that the average particle size Dv150 of the first active particles (ie, ternary material particles) of this embodiment is 1.0 μm.
[0180] Example 12
[0181] The difference between this embodiment and embodiment 1 is that the average particle size Dv150 of the first active particles (ie, ternary material particles) of this embodiment is 0.5 μm.
[0182] Embodiment 13
[0183] The difference between this embodiment and the first embodiment is that the feeding speed, drying temperature, etc. change the particle size of the intermediate powder so that the average particle size Dv50 of the positive electrode active particles 100 is 7 μm.
[0184] Embodiment 14
[0185] The difference between this embodiment and the first embodiment is that the feeding speed, drying temperature, etc. change the particle size of the intermediate powder so that the average particle size Dv50 of the positive electrode active particles 100 is 6 μm.
[0186] Embodiment 15
[0187] The difference between this embodiment and the first embodiment is that the particle size of the intermediate powder is changed by the feeding speed, the drying temperature, etc. so that the average particle size Dv50 of the positive electrode active particles 100 is 5 μm.
[0188] Example 16
[0189] The difference between this embodiment and the first embodiment is that the feeding speed, drying temperature, etc. change the particle size of the intermediate powder so that the average particle size Dv50 of the positive electrode active particles 100 is 4 μm.
[0190] Embodiment 17
[0191] The difference between this embodiment and the first embodiment is that the amount of the pyrrole monomer is changed so that the thickness h2 of the coating layer 30 is 2 μm.
[0192] Embodiment 18
[0193] The difference between this embodiment and the first embodiment is that the amount of the pyrrole monomer is changed so that the thickness h2 of the coating layer 30 is 3 μm.
[0194] Embodiment 19
[0195] The difference between this embodiment and the first embodiment is that the amount of the pyrrole monomer is changed so that the thickness h2 of the coating layer 30 is 4 μm.
[0196] Embodiment 20
[0197] The difference between this embodiment and embodiment 1 is that the first solid electrolyte, the second solid electrolyte, the third solid electrolyte, the fourth solid electrolyte and the fifth solid electrolyte of this embodiment are all Li2S-P2S5.
[0198] Embodiment 21
[0199] The difference between this embodiment and embodiment 1 is that the first solid electrolyte, the second solid electrolyte, the third solid electrolyte, the fourth solid electrolyte and the fifth solid electrolyte of this embodiment are all Li2S-SiS2-P2S5-LiI.
[0200] Comparative Example 1
[0201] The preparation method of the solid-state battery 300 of this comparative example includes:
[0202] 1) Preparation of positive electrode sheet 200: LiNi and 0.6 Co 0.2 Mn 0.2 O2 (ternary material particles), lithium manganese iron phosphate material, graphene (positive electrode conductive agent), and PVDF (positive electrode binder) are mixed evenly in a stirring tank, and a solvent N-methylpyrrolidone (NMP) is added to obtain a uniform slurry. The slurry is coated on the positive electrode current collector 210 aluminum foil and vacuum dried in a vacuum drying oven at 150°C for 15 hours to obtain a positive electrode sheet 200. The positive electrode sheet 200 is cut by a focused ion beam, and the cross-sectional morphology of the positive electrode sheet 200 is observed by a scanning electron microscope. Fig.11 .
[0203] Weigh Li according to the mass ratio of 95:5 1.3 Al 0.3 Ti 1.7 The (PO4)3 layer (fifth solid electrolyte) is mixed with PVDF binder and NMP to make a slurry, which is then coated on the positive electrode plate 200 and dried to obtain a stacked solid electrolyte layer 310 / positive electrode plate 200.
[0204] 2) Assembly of solid-state battery 300: Assemble in a glove box in the order of positive electrode shell, solid electrolyte layer 310 / positive electrode plate 200, lithium plate (negative electrode plate 320), stainless steel gasket, spring, and negative electrode shell, and place on a sealing machine to encapsulate to obtain a CR2032 button battery.
[0205] Comparative Example 2
[0206] The method for preparing the solid-state battery 300 of this embodiment includes:
[0207] 1) Preparation of positive electrode active particles 100:
[0208] ① Lithium iron manganese phosphate material (LiMn 0.6 Fe 0.4 PO4, Dv250 particle size is 0.3μm, namely the second active particles and the third active particles), Li 1.3 Al 0.3 Ti1.7 (PO4)3 (first solid electrolyte and second solid electrolyte), polyvinylidene fluoride PVDF (first binder and second binder) are mixed evenly, N-methylpyrrolidone (NMP) is added as a solvent, stirred evenly, and then LiNi is gradually added. 0.6 Co 0.2 Mn 0.2 O2 (ternary material particles, i.e., the first active particles, Dv150 is 3 μm), and continue to stir evenly to obtain a uniformly mixed slurry; wherein, the ternary material particles, lithium manganese iron phosphate material, Li 1.3 Al 0.3 Ti 1.7 The mass ratio of (PO4)3 and PVDF is 55:30:10:5.
[0209] ② The slurry is spray dried (the pump speed is 10 mL / min, and the drying temperature is set to 200° C.) to form an intermediate powder with a certain particle size, wherein the intermediate powder includes an active core 10 and an adhesion layer 20 .
[0210] 2) Preparation of positive electrode sheet 200:
[0211] The positive electrode active particles 100, Li 1.3 Al 0.3 Ti 1.7 (PO4)3 (fourth solid electrolyte), graphene (positive electrode conductive agent), and PVDF (positive electrode binder) are mixed evenly in a stirring tank, and a solvent N-methylpyrrolidone (NMP) is added to obtain a uniform slurry, which is coated on a positive electrode current collector 210 aluminum foil, and vacuum dried in a vacuum drying oven at 150° C. for 15 h to obtain a positive electrode sheet 200;
[0212] Weigh Li according to the mass ratio of 95:5 1.3 Al 0.3 Ti 1.7 The (PO4)3 layer (fifth solid electrolyte) is mixed with PVDF binder and NMP to make a slurry, which is then coated on the positive electrode plate 200 and dried to obtain a stacked solid electrolyte layer 310 / positive electrode plate 200.
[0213] 3) Assembly of solid-state battery 300:
[0214] The positive electrode shell, solid electrolyte layer 310 / positive electrode plate 200, lithium plate (negative electrode plate 320), stainless steel gasket, spring and negative electrode shell are assembled in the glove box in this order and placed on a sealing machine to obtain a CR2032 button cell.
[0215] The solid-state battery 300 of each embodiment and comparative example was subjected to performance tests:
[0216] (1) Thickness h1 of the adhesion layer 20 and thickness h2 of the coating layer 30: measured using a transmission electron microscope.
[0217] (2) Dv150, Dv50: measured using a scanning electron microscope (SEM).
[0218] (3) Rate discharge capacity test:
[0219] At 25° C., the solid-state battery 300 prepared in the embodiment and the comparative example was charged at a rate of 0.1C to a voltage of 2.5V, and then discharged at a rate of 0.1C to a voltage of 4.3V, which was recorded as the 0.1C discharge capacity.
[0220] (4) Cyclic performance test:
[0221] The solid-state battery 300 was subjected to a charge and discharge cycle test on a charge and discharge instrument (Nebula Charge and Discharge Test System - BAT-NEEFLCT-05300-V010). The test temperature was 25°C, the cycle rate was 1C (i.e., both the charge rate and the discharge rate were 1C), the charging voltage was 2.5V to 4.3V, and the capacity retention rate after 200 cycles was calculated. The cycle capacity retention rates of the solid-state batteries 300 of each embodiment and comparative example after 200 cycles at 25°C and a charge and discharge rate of 1C are shown in Table 1 below.
[0222] The capacity retention rate of the 25°C cycle is calculated as follows: capacity retention rate after the nth cycle = (discharge capacity after the nth cycle / discharge capacity of the first cycle) × 100%.
[0223] Table 1 Performance parameters of the solid-state battery 300 of each embodiment and comparative example
[0224]
[0225] It can be seen from the test results of Example 1 and Comparative Example 1 that, compared with the solid-state battery 300 of Comparative Example 1, the solid-state battery 300 of Example 1 has a higher discharge capacity and a higher cycle capacity retention rate. Fig.11 It can be seen that the particles in the positive electrode active layer 220 of Comparative Example 1 have low density and uneven distribution, which easily leads to poor contact. Therefore, the solid-state battery 300 of Comparative Example 1 has a lower discharge capacity and a lower cycle capacity retention rate.
[0226] From the test results of Example 1 and Comparative Example 2 in Table 1, it can be seen that compared with the positive electrode active particles 100 without the coating layer 30 in Comparative Example 2, the solid-state battery 300 of the present embodiment has a higher discharge capacity and a higher cycle capacity retention rate. This is because the positive electrode active particles 100 of Example 1 of the present application have a coating layer 30, and the coating layer 30 includes polypyrrole and Li1.3 Al 0.3 Ti 1.7 (PO4)3 (third solid electrolyte), polypyrrole is a fibrous conductive polymer, and the strong binding force of the conductive fibers entangled with each other can improve the overall mechanical strength of the positive electrode active particles 100 and inhibit the breakage of the positive electrode active particles 100; in addition, Li 1.3 Al 0.3 Ti 1.7 (PO4)3 can accelerate lithium ion transmission and reduce interface impedance, thereby improving the capacity performance and capacity retention rate of the solid-state battery 300.
[0227] It can be seen from the test results of Examples 1 to 4 in Table 1 that, as the content of the ternary material particles in the positive electrode active particles 100 increases, the discharge capacity of the solid-state battery 300 first gradually increases and then gradually decreases. This is because as the content of the ternary material particles in the positive electrode active particles 100 increases, the overall capacity of the positive electrode active particles 100 increases; in addition, as the content of the ternary material particles increases, the corresponding amount of lithium iron manganese phosphate added decreases, so that the gaps between the ternary material particles cannot be fully filled and stacked, reducing the contact area between the ternary material particles and the thickness of the adhesion layer 20, thereby reducing the conductive effect brought by the lithium iron manganese phosphate material and the buffering effect of the adhesion layer 20. Therefore, when the active core 10 includes 55% to 65% of the first active particles (ternary material particles) and 20% to 30% of the second active particles by mass fraction, the solid-state battery 300 can have a higher discharge capacity and cycle capacity retention rate.
[0228] From the test results of Example 1, Example 5 to Example 7 in Table 1, it can be seen that as the Li 1.3 Al 0.3 Ti 1.7 As the amount of (PO4)3 added gradually decreases, the discharge capacity of the solid-state battery 300 gradually decreases, and the cycle capacity retention rate also gradually decreases. This is because Li 1.3 Al 0.3 Ti 1.7 (PO4)3 can construct a lithium ion transmission channel. 1.3 Al 0.3 Ti 1.7 When the content of (PO4)3 is too low, the transmission speed of lithium ions is reduced, thereby reducing the discharge capacity and cycle capacity retention rate of the solid-state battery 300. 1.3 Al 0.3 Ti 1.7 When the mass fraction of (PO4)3 is 5% to 10%, the solid-state battery 300 can have a higher discharge capacity and a higher cycle capacity retention rate.
[0229] From Example 1, Example 8 to Example 12 in Table 1, the average particle size Dv150 of the ternary material particles gradually decreases, the discharge capacity of the solid-state battery 300 first gradually increases and then gradually decreases, and the cycle capacity retention rate of the solid-state battery 300 also first gradually increases and then gradually decreases. This is because when the average particle size Dv150 of the ternary material particles is small, when the ternary material particles are mixed with the lithium iron manganese phosphate material, there will be partial particle enrichment, and the adhesion layer 20 with the lithium iron manganese phosphate material cannot be formed, thereby reducing the electronic conductivity of the positive electrode active particles 100 and affecting the capacity of the positive electrode active particles 100. Therefore, when the average particle size Dv150 of the ternary material particles is 1μm to 3μm, the solid-state battery 300 can have a higher discharge capacity and a higher cycle capacity retention rate.
[0230] From the test results of Example 1, Example 13 to Example 16 in Table 1, it can be seen that as the average particle size Dv50 of the positive electrode active particles 100 increases, the discharge capacity of the solid-state battery 300 first gradually increases and then gradually decreases, and the cycle capacity retention rate of the solid-state battery 300 also first gradually increases and then gradually decreases. This is because if the average particle size Dv50 of the positive electrode active particles 100 is too small, there are structural defects inside the positive electrode active particles 100, such as incomplete coating of the adhesion layer 20, uneven distribution of the coating layer 30, etc., so that the positive electrode active particles 100 are prone to breakage during repeated charging and discharging, thereby reducing the discharge capacity and cycle capacity retention rate of the solid-state battery 300; when the average particle size Dv50 of the positive electrode active particles 100 is too large, the migration path of lithium ions is increased, thereby hindering the migration of lithium ions, resulting in a decrease in the capacity of the positive electrode active particles 100, and the discharge capacity and cycle capacity retention rate of the solid-state battery 300 are also reduced. Therefore, when the average particle size Dv50 of the positive electrode active particles 100 is 5 μm to 8 μm, the solid-state battery 300 can have a higher discharge capacity and a higher cycle capacity retention rate.
[0231] From the test results of Example 1, Example 17 to Example 19 in Table 1, it can be seen that as the thickness h2 of the coating layer 30 of the positive electrode active particle 100 increases, the discharge capacity and cycle capacity retention rate of the solid-state battery 300 first gradually increase and then gradually decrease. This is because when the thickness h2 of the coating layer 30 is too thin, the binding force of the coating layer 30 on the active core 10 and the adhesion layer 20 is insufficient, making the positive electrode active particle 100 easy to break during repeated charging and discharging; when the thickness h2 of the coating layer 30 is too thick, the transmission path of the ions becomes longer, the ion diffusion rate decreases, and the kinetic performance deteriorates.
[0232] From the test results of Example 1, Example 20 and Example 21 in Table 1, it can be seen that when the positive electrode active particles 100 use sulfide solid electrolytes, the solid-state battery 300 has a higher discharge capacity and cycle capacity retention rate than when using oxide solid electrolytes. This is because the sulfide solid electrolyte has higher deformability and ion conductivity, which can better promote the electrical performance of the positive electrode active particles 100.
[0233] Mentioning "embodiment" and "implementation method" in this application means that the specific features, structures or characteristics described in conjunction with the embodiment may be included in at least one embodiment of the present application. The appearance of the phrases in various places in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described in this application can be combined with other embodiments. In addition, it should also be understood that the features, structures or characteristics described in the various embodiments of the present application can be arbitrarily combined to form another embodiment that does not deviate from the spirit and scope of the technical solution of the present application, provided that there is no contradiction between them.
[0234] Finally, it should be noted that the above implementation modes are only used to illustrate the technical solution of the present application and are not intended to limit it. Although the present application has been described in detail with reference to the above preferred implementation modes, a person of ordinary skill in the art should understand that the technical solution of the present application may be modified or replaced by equivalents without departing from the spirit and scope of the technical solution of the present application.
Claims
1. A positive electrode active particle, characterized in that: The positive electrode active particles include: An active core, the active core comprising first active particles, second active particles and a first solid electrolyte, the average particle size of the first active particles being larger than the average particle size of the first solid electrolyte, and the average particle size of the first solid electrolyte being larger than the average particle size of the second active particles; an adhesion layer, the adhesion layer wrapping the surface of the active core; and The coating layer is wrapped around the surface of the adhesion layer.
2. The positive electrode active particle according to claim 1, characterized in that: The average particle size of the first active particles is Dv150, and the average particle size of the second active particles is Dv250, then 0.07≤Dv250 / Dv150≤0.
4.
3. The positive electrode active particle according to claim 1, characterized in that: The average particle size of the first active particles is Dv150, and the average particle size of the first solid electrolyte is Dv350, then 0.1≤Dv350 / Dv150≤0.
5.
4. The positive electrode active particle according to claim 1, characterized in that: The average particle size Dv150 of the first active particles is in the range of 1 μm ≤ Dv150 ≤ 3 μm; the average particle size Dv250 of the second active particles is in the range of 0.2 μm ≤ Dv250 ≤ 0.5 μm; the average particle size Dv350 of the first solid electrolyte is in the range of 0.3 μm ≤ Dv350 ≤ 0.6 μm.
5. The positive electrode active particle according to claim 1, characterized in that: The gram capacity of the first active particles is greater than that of the second active particles, the first active particles include ternary material particles, and the second active particles include lithium manganese iron phosphate particles.
6. The positive electrode active particle according to claim 5, characterized in that: The chemical formula of the ternary material particles includes LiNi x Co y Mn 1-x-y O2, wherein x ranges from 0.6 to 0.9 and y ranges from 0.05 to 0.
35.
7. The positive electrode active particle according to claim 1, characterized in that: The active core also includes a first binder, and the active core includes, by mass fraction, 55% to 65% of the first active particles, 20% to 30% of the second active particles, 5% to 10% of the first solid electrolyte, and 5% to 10% of the first binder.
8. The positive electrode active particle according to claim 1, characterized in that: The first solid electrolyte includes at least one of an oxide solid electrolyte and a sulfide solid electrolyte; the oxide solid electrolyte includes Li 1.3 Al 0.3 Ti 1.7 (PO4)3; the sulfide solid electrolyte includes at least one of Li2S-P2S5, Li2S-SiS2-P2S5-LiI.
9. The positive electrode active particle according to claim 1, characterized in that: The adhesion layer includes 60% to 80% of third active particles, 10% to 35% of second solid electrolyte and 5% to 10% of second binder by mass.
10. The positive electrode active particle according to claim 9, characterized in that: The third active particles include lithium manganese iron phosphate particles, the second solid electrolyte includes at least one of an oxide solid electrolyte and a sulfide solid electrolyte; the oxide solid electrolyte includes Li 1.3 Al 0.3 Ti 1.7 (PO4)3; the sulfide solid electrolyte includes at least one of Li2S-P2S5, Li2S-SiS2-P2S5-LiI.
11. The positive electrode active particle according to claim 9, characterized in that: The thickness h1 of the adhesion layer is in the range of 0.5 μm≤h1≤0.8 μm.
12. The positive electrode active particle according to any one of claims 1 to 11, characterized in that: The coating layer includes 5% to 10% of a third solid electrolyte and 90% to 95% of a conductive polymer by mass.
13. The positive electrode active particle according to claim 12, characterized in that: The third solid electrolyte includes at least one of an oxide solid electrolyte and a sulfide solid electrolyte; the oxide solid electrolyte includes Li 1.3 Al 0.3 Ti 1.7 (PO4)3; the sulfide solid electrolyte includes at least one of Li2S-P2S5, Li2S-SiS2-P2S5-LiI; the conductive polymer includes at least one of polypyrrole, polyaniline, and polyacetylene.
14. The positive electrode active particle according to claim 12, characterized in that: The thickness h2 of the coating layer is in the range of 1 μm≤h2≤3 μm.
15. The positive electrode active particle according to any one of claims 1 to 11, 13 and 14, characterized in that: The average particle size Dv50 of the positive electrode active particles is in the range of 5 μm≤Dv50≤8 μm.
16. A positive electrode plate, characterized in that: include: Positive electrode current collector; as well as A positive electrode active layer, wherein the positive electrode active layer is disposed on the surface of the positive electrode current collector, and the positive electrode active layer comprises the positive electrode active particles according to any one of claims 1 to 15.
17. A solid-state battery, characterized in that: include: The positive electrode sheet, solid electrolyte layer and negative electrode sheet as described in claim 16; the solid electrolyte layer is located between the positive electrode sheet and the negative electrode sheet.